Animal tracks & signs - Johnson, Jinny; Burton, John A. (Washington, D.C. : National Geographic, 2008)
Presents an illustrated guide to how to interpret tracks and sign from over four hundred animals, covering droppings and pellets, dens, nests, and other indications of behavior, with diagrams and information on different animals' range, habitat, and food.
"More than 400 animals from big cats to backyard birds"--Cover.
"A Marshall edition"--P. facing t.p.
Includes bibliographical references (p. 188) and index.
6.7
5-8
Keywords: Animal tracks -- Juvenile literature; Animals -- Habitations -- Juvenile literature; Animal behavior -- Juvenile literature; Animal tracks; Animals -- Habitations; Animal behavior; Animal tracks; Animals -- Habitations; Animal behavior